An interactive algorithm to graph the michaelis-menten equation - Trujillo Arriaga, Héctor Miguel (Revista Mexicana de Ingenieria Biomedica, 2018)
An interactive algorithm is presented for the graphing of the Michaels - Menten equation, which is widely used in Enzymatic Dynamics studies. It also proposes the introduction of other parameters different from those commonly used (Vm, Km), but complementary, which provide more information.